Suppression of Fusarium wilt in Cyclamen by using sage water extract and identification of antifungal metabolites - Ahmad, H.; Matsubara, Y. (Australasian plant pathology, 2020)
In the present study, the in vitro antifungal potential of seven Lamiaceae herbs against Fusarium oxysporum f. sp. cyclaminis were investigated. On the basis of the results, the in vivo antifungal effects of sage water extract on Fusarium wilt in cyclamen were evaluated, and the antifungal properties of the extract were identified. Among the seven herbs, sage water extract (0.5% and 2%, w / v ) showed considerable suppression of F. oxysporum f. sp. cyclaminis in vitro. For the in vivo evaluation, cyclamen plants were treated with sage water extract (20%, w / v ) two times and inoculated with F. oxysporum f. sp. cyclaminis . Six weeks after the inoculation, a lower disease incidence and disease severity indices were observed in roots and shoots of the treated plants. These effects could be attributed to reduced Fusarium populations in the plant roots because of the fungistatic and fungicidal effects of the sage extract. Consequently, the dry weights of the shoots and roots treated with the sage extract were higher than those of the control. Ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS) was performed, and caffeic acid and rosmarinic acid were identified to be important metabolites in the sage water extract. In addition, the antifungal effects of these compounds against F. oxysporum f. sp. cyclaminis were confirmed using an in vitro test. Thus, it can be concluded that sage water extract can suppress Fusarium wilt in cyclamen and the two identified compounds play key roles in the antifungal properties of sage.